Risk factors for recurrence in patients with Clostridium difficile infection due to 027 and non-027 ribotypes. (April 2019) - Falcone, M.; Tiseo, G.; Iraci, F.; Raponi, G.; Goldoni, P.; Delle Rose, D.; Santino, I.; Carfagna, P.; Murri, R.; Fantoni, M.; Fontana, C.; Sanguinetti, M.; et al.
Abstract: Objectives: Our objective was to evaluate factors associated with recurrence in patients with 027+ and 027– Clostridium difficile infection (CDI). Methods: Patients with CDI observed between January and December 2014 in six hospitals were consecutively included in the study. The 027 ribotype was deduced by the presence of tcdB, tcdB, cdt genes and the deletion Δ117 in tcdC (Xpert® C. difficile /Epi). Recurrence was defined as a positive laboratory test result for C. difficile more than 14 days but within 8 weeks after the initial diagnosis date with reappearance of symptoms. To identify factors associated with recurrence in 027+ and 027– CDI, a multivariate analysis was performed in each patient group. Subdistributional hazard ratios (sHRs) and 95% confidence intervals (95%CIs) were calculated. Results: Overall, 238 patients with 027+ CDI and 267 with 027– CDI were analysed. On multivariate analysis metronidazole monotherapy (sHR 2.380, 95%CI 1.549–3.60, p <0.001) and immunosuppressive treatment (sHR 3.116, 95%CI 1.906–5.090, p <0.001) were factors associated with recurrence in patients with 027+ CDI. In this patient group, metronidazole monotherapy was independently associated with recurrence in both mild/moderate (sHR 1.894, 95%CI 1.051–3.410, p 0.033) and severe CDI (sHR 2.476, 95%CI 1.281–4.790, p 0.007). Conversely, non-severe disease (sHR 3.704, 95%CI 1.437–9.524, p 0.007) and absence of chronic renal failure (sHR 16.129, 95%CI 2.155–125.000, p 0.007) were associated with recurrence in 027– CDI. Conclusions: Compared to vancomycin, metronidazole monotherapy appears less effective in curing CDI without relapse in the 027+ patient group, independently of disease severity.